2020
DOI: 10.5424/sjar/2020182-15551
|View full text |Cite
|
Sign up to set email alerts
|

Pollen tube growth and fruit set in quince (Cydonia oblonga Mill.)

Abstract: Aim of study: To determine the self-compatibility level of eight quince cultivars.Area of study: The region of Belgrade (Central Serbia).Material and methods: Pollen tube growth in vivo and fruit set in two pollination variants (self- and open-pollination) were studied in eight quince cultivars. The quantitative parameters of pollen tube growth (average number of pollen tubes in the upper and middle third of the style, base of the style and in the ovary; the dynamics of pollen tube growth through these parts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…These results suggest that quince can exhibit both self-incompatibility and self-compatibility. This finding is consistent with previous studies by Tatari et al [ 24 ] and Radović et al [ 25 ], which reported that quince can exhibit different levels of self-incompatibility in various cultivars. Radović et al [ 25 ] found that ’Leskovacka’ and ’Vranjska’ were self-compatible cultivars, while the others were self-incompatible.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results suggest that quince can exhibit both self-incompatibility and self-compatibility. This finding is consistent with previous studies by Tatari et al [ 24 ] and Radović et al [ 25 ], which reported that quince can exhibit different levels of self-incompatibility in various cultivars. Radović et al [ 25 ] found that ’Leskovacka’ and ’Vranjska’ were self-compatible cultivars, while the others were self-incompatible.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with previous studies by Tatari et al [ 24 ] and Radović et al [ 25 ], which reported that quince can exhibit different levels of self-incompatibility in various cultivars. Radović et al [ 25 ] found that ’Leskovacka’ and ’Vranjska’ were self-compatible cultivars, while the others were self-incompatible. In contrast, the recent study by Radović et al [ 26 ] found that incompatible pollen tubes were present in both self-pollination and open pollination, andthat only ’Leskovacka’ and ’Vranjska’ were self-compatible.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…An earlier study on the same cultivars included a detailed analysis of the number of pollens tubes in the pistil and style, but also of the dynamics of pollen tube growth by pistil regions. Based on these results, 'Leskovacka' and 'Vranjska' were found to be self-compatible, while other cultivars ('Morava', 'Pazardzijska', 'Hemus', 'Asenica', 'Portugal' and 'Triumph') were self-incompatible (Radović et al, 2020). The study of incompatible pollen tubes in quince is a continuation of previous studies with the aim of analysing in detail the phenomenon of incompatibility in quince in two pollination modes (self-pollination and open pollination).…”
Section: Discussionmentioning
confidence: 94%
“…The cultivar is considered self-compatible if the pollen tubes during self-pollination reach the ovary in at least 25-30% of the pistils (Lopez et al, 2001). Based on the above, the cultivars 'Vranjska' and 'Leskovacka' are classified as self-compatible, while the other cultivars are classified as self-incompatible (Radović et al, 2020). Milatović and Nikolić (2007) and Milatović et al (2013b) consider as self-fertile those apricot cultivars in which at least one pollen tube reached the pistil in most of the analysed pistils.…”
Section: Results Results Resultsmentioning
confidence: 99%